COL11A1 is Downregulated by miR-339-5p and Promotes Colon Carcinoma Progression - Weizhi Liu; Ke Meng (Canadian Journal of Gastroenterology and Hepatology)
The roles of COL11A1 in cancer have been increasingly considered, but the understandings of the effects of COL11A1 on colon carcinoma progress are much limited yet. qRT-PCR and Western blot were utilized to evaluate COL11A1 expression at mRNA and protein levels, respectively, in colon carcinoma cell lines. Afterward, the tumorigenesis biological effects of COL11A1 were examined by CCK-8, colony formation, Transwell, and wound healing methods. Moreover, upstream miRNAs containing the binding sites with COL11A1 were predicted by the bioinformatics methods. The interplay between COL11A1 and miR-339-5p was identified by a dual-luciferase assay. COL11A1 expression was prominently upregulated in colon carcinoma cell lines relative to that in normal human colon mucosal epithelial cell lines, and it was related to tumor stages. The outcomes of in-vitro experiments suggested that interfering with COL11A1 remarkably repressed the malignant behaviors of SW480 and SW620 cells. MiR-339-5p was markedly lowly expressed in colon carcinoma cell lines. Furthermore, miR-339-5p directly targeted and negatively regulated COL11A1 expression. COL11A1 upregulation promoted colon carcinoma cell functions, while overexpressing miR-339-5p evidently attenuated the promotion. These results proved the modulation of the miR-339-5p/COL11A1 axis in colon carcinoma cells, and miR-339-5p repressed colon carcinoma progression via COL11A1 downregulation. These results offer new underlying targets for the accurate therapy of colon carcinoma patients.